POSISI PEKERJA MIGRAN INDONESIA ILEGAL (PMI) ASAL SULAWESI SELATAN SEBAGAI PIHAK SUB-ALTERN DI MALAYSIA - Nur Rahmi Oktaviani R; Aspin Nur Arifin Rivai (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2024)
The aim of this research is to evaluate the state policies related to illegal migrant workers from South Sulawesi in Malaysia and to analyze the reasons behind the subordination of illegal migrant workers by the state through institutional instruments, despite their rights that should be protected by the state. By using the concept of Human Security to assess the fulfillment of migrant workers' rights and Critical Theory to examine the policies of handling illegal immigrants by Indonesia and Malaysia, this research relies on primary data from interviews with two informants and secondary data from relevant documents. The results of the research indicate that the rights of migrant workers in Indonesia have not been fully met, especially for illegal migrant workers who do not go through the BP2MI procedure. While the rights of legal migrant workers are more fulfilled because they follow the procedure, BP2MI is constrained by the Constitution in touching the individual rights of illegal migrant workers. The implications of this research include: 1) The need for Indonesia to tighten the Constitution regarding migrant workers, 2) The importance of society following the BP2MI procedure to ensure rights as legal migrant workers, and 3) The need for further research on the topic of migrant workers.